Appraisal of Total Phenol, Flavonoid Contents, and Antioxidant Potential of Folkloric Lannea coromandelica Using In Vitro and In Vivo Assays. (17th September 2015) - Kumar, Tekeshwar; Jain, Vishal
Abstract : The aim of this study was to determine the impending antioxidant properties of different extracts of crude methanolic extract (CME) of leaves of Lannea coromandelica ( L. coromandelica ) and its two ethyl acetate (EAF) and aqueous (AqF) subfractions by employing various established in vitro systems and estimation of total phenolic and flavonoid content. The results showed that extract and fractions possessed strong antioxidant activity in vitro and among them, EAF had the strongest antioxidant activity. EAF was confirmed for its highest phenolic content, total flavonoid contents, and total antioxidant capacity. The EAF was found to show remarkable scavenging activity on 2, 2-diphenylpicrylhydrazyl (DPPH) (EC50 63.9 ± 0.64 µ g/mL), superoxide radical (EC50 8.2 ± 0.12 mg/mL), and Fe 2+ chelating activity (EC50 6.2 ± 0.09 mg/mL). Based on our in vitro results, EAF was investigated for in vivo antioxidant assay. Intragastric administration of the EAF can significantly increase levels of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and glutathione peroxidase (GSH-Px) levels, and decrease malondialdehyde (MDA) content in the liver and kidney of CCl4 -intoxicated rats. These new evidences show that L. coromandelica bared antioxidant activity.